Electrochemical profiling and liquid chromatography–mass spectrometry characterization of synthetic cathinones: From methodology to detection in forensic samples. Issue 7 (3rd March 2021) - Schram, Jonas; Parrilla, Marc; Sleegers, Nick; Van Durme, Filip; van den Berg, Jorrit; van Nuijs, Alexander L. N.; De Wael, Karolien
Abstract: The emergence of new psychoactive drugs in the market demands rapid and accurate tools for the on‐site classification of illegal and legal compounds with similar structures. Herein, a novel method for the classification of synthetic cathinones (SCs) is presented based on their electrochemical profile. First, the electrochemical profile of five common SC (i.e., mephedrone, ethcathinone, methylone, butylone, and 4‐chloro‐alpha‐pyrrolidinovalerophenone) is collected to build calibration curves using square wave voltammetry on graphite screen‐printed electrodes (SPEs). Second, the elucidation of the oxidation pathways, obtained by liquid chromatography–high‐resolution mass spectrometry, allows the pairing of the oxidation products to the SC electrochemical profile, providing a selective and robust classification. Additionally, the effect of common adulterants and illicit drugs on the electrochemical profile of the SC is explored. Interestingly, a cathodic pretreatment of the SPE allows the selective detection of each SC in presence of electroactive adulterants. Finally, the electrochemical approach is validated with gas chromatography–mass spectrometry by analyzing 26 confiscated samples from seizures and illegal webshops. Overall, the electrochemical method exhibits a successful classification of SC including structural derivatives, a crucial attribute in an ever‐diversifying drug market. Abstract : A novel on‐site testing approach for the classification of synthetic cathinones in seizures is presented. The concept is based on electrochemical methods that use screen‐printed electrodes for the determination of the electrochemical profile. The method is assessed with common cutting agents and finally validated with 26 street samples from forensic laboratories.